Educação musical interativa: recursos da musica visual para as tecnologias educacionais em rede - Gonçalves, Jair dos Santos (2015)
This research has the objective to carry out scientific studies, through which, we can reflect on interactive techno-aesthetic objects and the production thereof in order to explore their interdisciplinary possibilities for the area of music education within perspectives of Contemporary Art and Educational Technology Network. With empirical / qualitative, this research continues the investigations carried out by the Student Orchestra in a public school in the state of Rio Grande do Sul. Aiming at an interdisciplinary contribution between the areas of Visual Arts and Music, with mediation by the Information and Communication Network, seeks to provide reflections on music education mediated by ICT. Narratives of sound production proposals were developed by means of sound-musical interpretation activities, based on imagery resources for Visual Music Productions. The discussion of political, economic and conscientious use of the Internet, with the methodological procedures for the appraisal of musical scenes of daily life activities, it is also one of the purposes of this research. The final product of this research is the development of methodologies for teaching proposals in Interactive Music Education, with the development of Visual Music Scripts and a composition with Visual Music Interactive, using the musical style of Free Improvisation.